002 Influence of a renal biopsy result on treatment and management of steroid-resistant, idiopathic nephrotic syndrome in children. (December 2018) - Webb, H; McKeever, S
Abstract : Background: Steroid-resistant nephrotic syndrome (SRNS) is the second biggest cause of childhood end-stage renal disease (ESRD). Renal biopsy is widely used as a classification tool in SRNS, but immunosuppression response and identification of disease-causing genetic mutations appear better predictors of those at risk of renal failure. A biopsy can, however, identify patients with SRNS caused by other diseases, which could necessitate a change in treatment. Aim: To explore whether renal biopsy results influence first line immunosuppression in childhood, idiopathic SRNS. Method: A service evaluation of children presenting with idiopathic SRNS was undertaken. Rates of change in treatment following renal biopsy were identified. Response rates to immunosuppression at twelve months and up to five years, and the rate of genetic mutations were obtained. Rates of ESRD were compared between different groups to identify predictors of renal failure. Results: Seventy-six children met the inclusion criteria. Two had a biopsy result that changed their first line management, although one also had a positive genetic mutation. At 12 months, 52 children (69%) were in complete remission, with a median time to remission 2 months, whilst 7 (9%) had a partial response, and 16 (21%) having no response to immunosuppression. Five children were identified with a positive genetic result. Nine patients (12%) developed ESRD, with response to immunosuppression appearing a better predictor than biopsy result (p=0.01 vs p=0.053 by Fisher's exact test). Conclusion: For most patients with idiopathic SRNS, first line immunosuppression is rarely changed as a result of the biopsy. Progression to ESRD is a risk for patients unresponsive to immunosuppression. A genetic screen should be carried out in all primary SRNS. Implications of this single centre study should be explored in other centres to assess the repeatability of results.